2022
DOI: 10.1097/mou.0000000000001041
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome, obesity and cancer risk

Abstract: Purpose of reviewThis review aims to report the latest discoveries regarding the relationship between BMI, obesity, and cancer development and treatment. Recent findingsObesity and metabolic syndrome relationships with cancer have been deeply investigated in the literature but their association is still debated. Currently, it has been recorded an association between BMI and endometrial, colorectal, gastric, liver, bladder, and prostate cancer. The mechanisms behind this association have also been investigated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 35 publications
0
14
0
1
Order By: Relevance
“…Diferentes estudios sugieren que la relación entre un IMC más alto y el cáncer puede incluir trastornos metabólicos comparables a los relacionados con el síndrome metabólico (SM) (Belladelli, F et al, 2022). A pasear de que se ha notado una asociación en forma de curva en J entre el IMC y el riesgo de mortalidad, aún no se tiene información precisa sobre el grado de aumento de la predisposición a la mortalidad relacionada con un aumento en el IMC, por ende, a continuación, se describen algunos de los parámetros de los criterios del SM asociados al IMC y las patologías más frecuentes relacionados (James, B. D., et al, 2018):…”
Section: Resultsunclassified
“…Diferentes estudios sugieren que la relación entre un IMC más alto y el cáncer puede incluir trastornos metabólicos comparables a los relacionados con el síndrome metabólico (SM) (Belladelli, F et al, 2022). A pasear de que se ha notado una asociación en forma de curva en J entre el IMC y el riesgo de mortalidad, aún no se tiene información precisa sobre el grado de aumento de la predisposición a la mortalidad relacionada con un aumento en el IMC, por ende, a continuación, se describen algunos de los parámetros de los criterios del SM asociados al IMC y las patologías más frecuentes relacionados (James, B. D., et al, 2018):…”
Section: Resultsunclassified
“…A Korean study [21] showed that participants with metabolic unhealth obesity had a higher risk of prostate cancer as well. The results of MetS and MUO on promoting the development of UC can be explained as follows: On the one hand, they share many common risk factors, including older age, obesity, lack of exercise, unhealthy diet, disturbance of the biological clock, oxidative stress, air pollution and damage caused by exposure to substances that disrupt the endocrine system [22,23]; on the other hand, chronic in ammation determined by obesity may concur to the development of tumours, and insulin resistance may directly or indirectly enhance cell proliferation [24].…”
Section: Discussionmentioning
confidence: 99%
“…11 Obesity is a prominent issue in contemporary society, not only leading to various chronic diseases (such as diabetes and cardiovascular diseases), 12 but also potentially associated with the development of several malignancies, including breast, bladder, and lung cancers. [13][14][15] There are multiple criteria for determining obesity, with clinical practice primarily measuring height and weight to approximate the proportion of body fat content, that is, using body mass index to assess obesity. 16 The liver plays a crucial role in fat metabolism, and numerous clinical studies have confirmed that the incidence of liver cancer has been rising in tandem with increasing rates of obesity in the population.…”
Section: Introductionmentioning
confidence: 99%